2006
DOI: 10.1007/s10750-005-1187-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variation of Cestode Infection and its Effects on Two Small Barbs (Barbus humilis and B. tanapelagius) in Lake Tana, Ethiopia

Abstract: Pseudophyllidean cestodes as Ligula have a complex life cycle with cyclopoid copepods as first intermediate host, zooplanktivorous fish as second, and piscivorous birds as final host. We studied the effects of diet, season and habitat occupation on the prevalence of plerocercoid larvae of the tapeworm Ligula intestinalis in two closely related small barbs and the effects of the parasites on the barbs life histories in Lake Tana (Ethiopia) during 1 year. In all affected barbs L. intestinalis caused retardation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 18 publications
3
16
1
2
Order By: Relevance
“…6b). Our results are, however, contrary to findings of Dejen et al (2006). These authors observed a decline in Ligula intestinalis infection and attributed this to a reduced uptake of plankton because of high turbidity.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…6b). Our results are, however, contrary to findings of Dejen et al (2006). These authors observed a decline in Ligula intestinalis infection and attributed this to a reduced uptake of plankton because of high turbidity.…”
Section: Discussioncontrasting
confidence: 99%
“…The host length was significantly correlated with A. macracantha and not with Bolbophorus sp. As reported in various studies from other species, larger fish harboured more endohelminths than smaller ones (Bell and Burt 1991;Poulin 1999;González and Acuña 2000;Fellis and Esch 2004;Dejen et al 2006). The positive correlation is explained by parasite accumulation in larger fish due to prolonged exposure and ontogenetic habitat and feeding shifts (Esch and Fernändez 1993;Paperna 1996;Marcogliese 2002).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Also, many researchers have studied some effects of this parasite for fish host such as growth, endocrine system, gonadal development and had determined that L. intestinalis was caused many pathogenic effect on host fish. The parasite can cause damage to the host fish specimens especially by compression and atrophy of vital organs including the gonads, liver in the coelomic cavity of the infected fish (Öztürk and Altınel, 2001;Jopling and Taylor, 2003;Oğuz et al, 2004;Carter et al, 2005;Hecker and Karbe, 2005;Dejen et al, 2006). Similarly, in present study, macroscopic investigations showed that stomachs of fish specimens were swollen and gonads were deformed.…”
Section: Resultssupporting
confidence: 68%